2014
DOI: 10.1055/s-0034-1371756
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of Living with a Stuttering Disorder: Knowing Is Not Enough

Abstract: Stuttering requires a multidimensional perspective given that, in recent years, researchers have shown the impact of the disorder to reach far beyond the surface components with demonstrated psychosocial and anxiety effects for the individual living with a stutter. This article explores the impact a stuttering disorder has on the individual (child, adolescent, and adult) and on their family members (siblings, parents, and partners). These experiences include behavioral and social difficulties, self-awareness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 61 publications
1
39
0
2
Order By: Relevance
“…This result is supported by some studies [19][20][21]. It is often necessary to pay considerable attention to advanced stutterers' negative feeling and attitudes in therapy [22,23]. So, besides the classic speech therapy procedures, additional psychological-based treatment and counseling should address problems possibly linked to the stuttering (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…This result is supported by some studies [19][20][21]. It is often necessary to pay considerable attention to advanced stutterers' negative feeling and attitudes in therapy [22,23]. So, besides the classic speech therapy procedures, additional psychological-based treatment and counseling should address problems possibly linked to the stuttering (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…(P16) No domínio de Profissionais da Saúde (e355) todos os participantes do G1 (n=20) consideraram o fonoaudiólogo como facilitador, por ajudá-los a enfrentar seu problema de fala. O participante P12 relata alguns aspectos abordados nas sessões Em relação aos Fatores Ambientais, relacionados primordialmente ao ambiente social e atitudinal, os resultados mostraram que nem sempre os familiares são facilitadores, achado semelhante a outro estudo 21 , o que reitera o impacto negativo nas relações familiares em algumas situações.…”
Section: Discussionunclassified
“…Further, stuttering severity has not been shown to relate to how much a speaker anticipates stuttering (Jackson et al, 2015) or their locus of control (De Nil & Kroll, 1995). While adolescents who exhibit mild stuttering behaviors may struggle to cope with stuttering and social interactions as much or more than those who stutter more frequently (Beilby, 2014), our findings challenge the results of other studies that have reported that higher stuttering severity is associated with lower self-perceived communication competence (Blood et al, 2001), lower social acceptance (Adriaensens et al, 2015), lower self-esteem (Adriaensens et al, 2015), greater social anxiety (Ezrati-Vinacour & Levin, 2004;Hollister, 2015), and more negative communication attitudes (Guttormsen et al, 2015). While our preliminary findings suggest that experience with stuttering did not influence how adolescents interpreted ambiguous social scenarios, there are likely individual differences in other cognitive and emotional processes that modulate the impact of stuttering on interpretation bias, above and beyond a diagnosis of stuttering or stuttering severity.…”
Section: Experience With Stuttering Did Not Influence Interpretationsmentioning
confidence: 99%
“…Stuttering is a multidimensional, neurodevelopmental communication disorder (A. Smith & Weber, 2017) that can deeply impact psychosocial outcomes for affected individuals (Beilby, 2014;Beilby, Byrnes, & Yaruss, 2012b;Boyle, 2015b;Briley, O'brien, & Ellis, 2019;Craig, Blumgart, & Tran, 2009;Erickson & Block, 2013;Yaruss & Quesal, 2006). Stuttering is characterized by an atypical frequency of stuttering-like disfluencies that interfere with the forward flow of speech including part-word repetitions (e.g., "a-a-and"), single-syllable word repetitions (e.g., "and-and"), prolongations (e.g., "aaaaand"), blocks (e.g., "---and"), and broken words (e.g., "o---pen") .…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 1 more Smart Citation